Comparison of Maximum Voluntary Contraction Positions for Serratus Anterior Muscle in Men with Scapular Dyskinesis: Electromyography Analysis - Mohammad Bayattork; Foad Seidi; Hooman Minoonejad; Arezoo Shahriarpour (Journal of Rehabilitation Sciences and Research, 2019)
Background: The purpose of this study was to quantify the surface EMG activity of the serratus anterior muscle during two main test positions performed with the maximum effort by the subjects with scapular dyskinesis. Methods: This cross-sectional study included 30 men (aged 18 to 28) who were suffering from scapular dyskinesis. Scapular dyskinesis was measured by scapular dyskinesis test and surface EMG was employed to record the EMG activity of the serratus anterior during two common positions of maximal voluntary isometric contraction. Results: The results revealed that there is no significant difference in the mean EMG activity of the serratus anterior muscle during two MVIC testing positions (P=0.846). Notably, the test-retest ICC scores for the EMG recordings during position 1 (P=0.97) and position 2 (P=0.96) were excellent. Conclusion: It was found that no one muscle test produced the highest MVIC for all subjects. Therefore, to perform normalization of every muscle within each subject, it is suggested that two tests identified in this study be performed which usually produce high levels of EMG activity.